Katalogisasi Bahan Pustaka di Perpustakaan Tanda Baca Pustaka Kabupaten Tangerang - Putri, Salsa Amalia; Rukmana, Evi Nursanti; Rohman, Asep Saeful (Institut Agama Islam Negeri Salatiga, 2023)
The purpose of this research is to explain the meaning of cataloging, analyze the processing of library materials, and carry out cataloging activities on library materials at Tanda Baca Pustaka Library Tangerang Regency. This research also discusses about Taman Bacaan Masyarakat (public reading park),, Online Public Access Catalog (OPAC), bibliography, and Senayan Library Management System (SLiMS). This research used descriptive qualitative method. The data collection techniques used in the research were literature study, observation, interviews, and documentation. The object studied was the processing of library materials at the Tanda Baca Library in Tangerang Regency, and the subject or informant was the manager of the Tanda Baca Library, Muhamaad Jaenudin. The results of the study show that the Tanda Baca Library has not processed its library materials. Researchers then carried out management activities by cataloging existing library materials using SLiMS. The process carried out is to enter various information on library materials in the bibliographic menu in SLiMS. From this process, the author managed to catalog 26 copies of books with 25 titles. Suggestions from researchers, Tanda Baca Pustaka Library can process its library materials so that the library is better managed and continues to grow. Tanda Baca Pustaka Library is also expected to continue to be processed, and managed properly because its existence is very beneficial for the surrounding community, especially children and teenagers.